Ultrasound diagnosis of bilateral cataracts in a fetus with possible cerebro-ocular congential muscular dystrophy during the routine second trimester anomaly scan. (August 2015) - Drought, Alexandra; Wimalasundera, Ruwan; Holder, Susan
The finding of bilateral congenital cataracts in the fetus is rare. We report bilateral congenital cataracts detected during the routine second trimester anomaly scan, which subsequently were found to be associated with other congenital anomalies and the parents opted for a termination of pregnancy. At post-mortem, Muscle–Eye Brain disease or Walker–Warburg Syndrome was considered likely, which are autosomal recessive congenital muscular dystrophy disorders associated with cerebral, cerebellar, muscle and eye anomalies. On ultrasound, bilateral cataracts appear as echogenic, solid areas within the fetal orbits. The examination of the fetal face and orbits plays an important role in confirming fetal well-being antenatally. We propose that it should become a routine part of the structural survey of fetal anatomy during the obstetric anomaly scan. This is especially important in pregnancies previously affected by fetal cataracts or pregnancies at risk of rare genetic syndromes.